Development and validation of Ayurveda based assessment scale for anxiety - Basavaraj R. Tubaki; G.S. Lavekar; C.R. Chandrashekar; T.N. Sathyaprabha; Bindu M. Kutty (Journal of Ayurveda and Integrative Medicine, 2023)
Background: Anxiety scale based on Ayurveda would help Ayurveda physicians to measure and initiate appropriate treatment strategies. Objectives: The objective of the study was to develop a clinical assessment scale for anxiety based on Ayurveda science. Materials and methods: Ayurveda assessment scale for anxiety (AAA) was developed and subjected to various psychometric evaluations. Patients of generalized anxiety disorder with social phobia (GAD with SP) (n = 31) meeting DSM-IV-TR criteria and age, sex-matched healthy subjects (n = 31) were enrolled from NIMHANS Psychiatry OPD. Two independent Ayurveda experts evaluated both patients and healthy subjects using AAA, Hamilton Anxiety Rating Scale (HARS), and Beck Anxiety Inventory (BAI). Reliability and validity assessments were carried out. The sensitivity to treatment-induced change was evaluated in a randomized controlled clinical trial. 72 patients of GAD with SP meeting DSM-IV-TR criteria, aged between 20 and 55 years, and either sex participated in the study. The duration of intervention was 30 days. The assessments were done through HARS, BAI, Beck Depression Inventory (BDI), AAA and Clinical Global Impression scales (Severity, Improvement, and Efficacy). Results: The Interrater reliability was between - good to very good score. Validity of AAA with HARS and BAI was significant (p < 0.001). Scales recorded significant differences when compared between patients and healthy subjects (p < 0.001). AAA also recorded the sensitivity to treatment-induced changes in a randomized controlled study and noted a large effect size (>0.60). Conclusions: The psychometric properties such as interrater reliability, validity (criteria, convergent, divergent, face) and sensitivity to change of AAA were promising.